CUPINS URBANOS (INSECTA, ISOPTERA) EM IMÓVEIS RESIDENCIAIS E NÃO RESIDENCIAIS DE MARANGUAPE II, PAULISTA, PERNAMBUCO, BRASIL. - Matias, Gicela Renê Rodrigues da Silva; Albuquerque, Auristela Correia de; Couto, Alane Ayana Vieira de Oliveira (Revista Nordestina de Zoologia, 2014)
Aiming to increase knowledge about the termite fauna present in urban areas, two hundred properties (100 residential and 100 non-residential) in the neighborhood of Maranguape II, Paulista, Pernambuco, Brazil, were inspected with the objective of locating termites or evidence of their activities. The economic losses resulting from the prevention, control and replacement of damaged materials were evaluated. Four species belonging to the families Kalotermitidae, Rhinotermitidae and Termtidae were found causing any harm. Nasutitermes corniger was the most frequent species, being present in 39% and 15% of residential and non residential buildings, respectively.